(untitled) (Analysis of International Sciences, 2024)
Culture plays an important role in shaping language and communication patterns, influencing how people interact, express themselves, and interpret messages. This abstract explores the complex relationship between culture, language and communication, highlighting how cultural norms, values, beliefs and practices influence language expressions and communication styles. By examining the influence of culture on language acquisition, language use, nonverbal communication, and intercultural communication, this abstract illuminates the complex interplay between culture and communication.